Sustainable development impact indicators for social and solidarity economy - Salathé-Beaulieu, Gabriel,Bouchard, Marie J.,Mendell, Marguerite (UNRISD, 2019)
The last decade has seen a growing interest in the measurement of the impact and performance of social and solidarity economy (SSE) organizations. This has been fuelled, among other things, by the rapid growth of the importance given to social enterprise, social entrepreneurship and impact investing in recent years. This paper, commissioned by the United Nations Research Institute for Social Development (UNRISD) as part of its Sustainable Development Performance Indicators project, attempts to review the methodologies, metrics and indicators implemented in the SSE today. Based on a review of the existing literature, it presents a selection of assessment tools and indicators that have been applied to SSE and so-called blended value enterprises since the 1990s. Some of the key approaches considered in this work include: the theory of change; the social accounting, reporting and auditing streams; various tools developed by the cooperative sector; the concept of
10419/246230
Keywords: Graue Literatur; Social and solidarity economy; Social enterprise; Social impact measurement; Evaluation; Theory of change; Utilité sociale; Social return on investment; Indicators; Sustainable Development Goals